2020
DOI: 10.21203/rs.3.rs-85373/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of renin–angiotensin–aldosterone system inhibitors with other antihypertensives in association with coronavirus disease-19 clinical outcomes

Abstract: Background: Reports on the effects of renin–angiotensin–aldosterone system (RAAS) inhibitors on the clinical outcomes of coronavirus disease-19 (COVID-19) have been conflicting. We performed this meta-analysis to find conclusive evidence. Methods: We searched published articles through PubMed, EMBASE and medRxiv from 5 January 2020 to 3 August 2020. Studies that reported clinical outcomes of patients with COVID-19, stratified by the class of antihypertensives, were included. Random and fixed-effects models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, in one study the use of RAASI was found to decrease the length of hospital stay [ 67 ]. Other studies including a study in which data was collected on 2,065,805 individuals [ 75 ] suggest a protective role of RAASI, decreasing the risk of severe illness and mortality [ 74 75 76 77 78 79 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in one study the use of RAASI was found to decrease the length of hospital stay [ 67 ]. Other studies including a study in which data was collected on 2,065,805 individuals [ 75 ] suggest a protective role of RAASI, decreasing the risk of severe illness and mortality [ 74 75 76 77 78 79 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six of the seven studies reporting subgroup analyses reported no difference in outcomes based on the type of RAASI [ 67 71 72 74 75 78 ], while only one study reported that taking ACEIs were better in decreasing the severity and mortality compared with those receiving ARBs [ 77 ].…”
Section: Resultsmentioning
confidence: 99%